(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The formation of civic education in modern Armenia is the most important and new civiliarchic factor for the democratic integration of the Armenian community into the global educational space, which is reinforced by the need of Armenian researchers for scientific understanding of the progressive experience of civic culture of the younger and older generations. The Constitution and laws of Armenia, public educational standards set strategic directions for state and local government bodies to humanize education, socialize schoolchildren and students, their self-identification through meaningful and democratic activities, the development of civil dialogue and partnership. Modernization, democratization and European integration presuppose the creation in schools, universities and other educational institutions of Armenia of conditions for the development of an individual with a high level of civic culture, the ability to independently make constructive decisions in a situation of choice, readiness for active participation in the life of civil society and government. In this context, there is a need for a theoretical substantiation of effective approaches of social science researchers to the formation of knowledge and skills of civic culture among schoolchildren, since it is at school age that the qualities of a conscious and responsible citizen develop. The promising areas for further research on this issue may be the following in modern Armenia: 1) new innovative technologies of cooperation between schools, universities, and civil society organizations (CSOs) in civic education; 2) anthropocentric models of civiliarchic partnership and dialogue of international organizations for the development of knowledge-based civic education; 3) the main directions of civic education in higher education, 4) civic education of young people in public institutions and political parties; 5) the development of new textbooks and teaching materials, the training of teachers to solve the problems of civic education.